Apple : the first 50 years - Pogue, David, 1963- (Simon & Schuster, 2026)
"In its first 50 years, Apple launched the personal computing revolution, brought art to the design of consumer machines, and changed the way we create, consume, and communitcate. Now, CBS Sunday Morning correspondent and veteran tech journalist David Pogue tells the full, true story: how Apple was born and nearly died; how Steve Jobs pulled off the greatest turnaround in corporate history; and how CEO Tim Cook continued the legacy, making Apple one of the most successful, influential, and controversial companies on earth. On April 1, 1976, two scruffy twentysomethings, both named Steve, founded a startup. Their goal: to bring the revolutionary power of computers to everyone. Over the next five decades, Apple reshaped the technology and cultural landscapes, introducing the public to breakthroughs such as the mouse, laser printing, CD-ROM, Wi-Fi, digital video, home networking, touchscreen phones, and tablets. Jobs's obsessive eye for detail set the standard for products that married advanced technology with beauty, simplicity, and fine design: Macintosh, iMac, iPod, iTunes, iPhone, iPad, AirPods, Apple Watch. Deeply researched and illustrated with 350 photos, Apple: The First 50 Years includes new interviews with 150 key people who made the journey, including Steve Wozniak, John Sculley, and Jony Ive, as well as designers, engineers, and executives, past and present. The book busts long-held myths, goes backstage for both the titanic successes (450 million iPods, 700 million iPads, 2.2 billion iPhones) and the instructive failures (Lisa, MobileMe, the Apple car), and assesses the forces that challenge Apple's dominance as it enters its second half century. Bursting with tales of frenetic all-nighters, engineering genius, and creative rebellion, this book is the definitive record of Apple's astonishing life story."--Book jacket flap.